Understanding international students’ experiences at university belonging in the Turkish higher education System: Insights from Gaziantep University - Ajjan, Bashar (Journal of International Students, 2026)
International students constitute a significant portion of the higher education population in Turkey. This study explores the sense of belonging of 20 international students selected through maximum diversity sampling from Gaziantep University. Using a qualitative content analysis, the study identifies three key factors that shape students’ sense of belonging: peer relationships, lecturers’ attitudes, and the overall educational environment. The findings highlight the value of fostering collaborative learning, expanding social activities, and promoting supportive, responsive instructor behavior. The study also recommends involving students in academic projects and research, establishing effective communication and feedback systems, simplifying university procedures, and supporting student clubs. The research emphasizes the need for inclusive university policies to enhance the academic and social integration of international students. To strengthen their sense of belonging, both structural and social reforms are needed to enable students to express themselves more fully and participate more fully in the university environment.